2012
DOI: 10.4161/auto.22110
|View full text |Cite
|
Sign up to set email alerts
|

Aurora kinase A inhibition-induced autophagy triggers drug resistance in breast cancer cells

Abstract: (2012) Aurora kinase A inhibition-induced autophagy triggers drug resistance in breast cancer cells,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
121
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 161 publications
(129 citation statements)
references
References 56 publications
6
121
1
1
Order By: Relevance
“…mTORC1 activation inhibited autophagy by abolishing phosphorylated ATG13 protein binding to ATG1, promoting the accumulation of p62 protein via reducing its degradation (59). Indeed, decrease the p62 expression by mTOR inhibitor was showed in some reports (8,60). Similarly, we found that expression of p62 decreased in mTOR inhibitors treated polyploidy cells (Fig.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…mTORC1 activation inhibited autophagy by abolishing phosphorylated ATG13 protein binding to ATG1, promoting the accumulation of p62 protein via reducing its degradation (59). Indeed, decrease the p62 expression by mTOR inhibitor was showed in some reports (8,60). Similarly, we found that expression of p62 decreased in mTOR inhibitors treated polyploidy cells (Fig.…”
Section: Discussionsupporting
confidence: 61%
“…5). We previously showed that Aurora inhibition induced autophagy and triggered drug resistance, which could be reversed by autophagy inhibitors (8). These paradoxical data suggested that cell death or survival promoted by autophagy depended on the physiologic state of the cell (47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymorphisms in the AURKA gene have been shown to increase the risk of primary breast cancer (26). Studies have revealed that the increased expression of AURKA is associated with laryngeal, nasopharyngeal and breast cancer metastasis (27)(28)(29)(30). AURKA has been demonstrated to be accountable for the phosphorylation of Breast Cancer 1, Early Onset (BRCA1) (31).…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is one of the main signs of effective anticancer chemotherapy; however, due to drug resistance, the apoptotic effects of drugs on the tumor cells are weakened and a large proportion of patients respond poorly to chemotherapy (19,20). At present, drug resistance of tumor cells is one of the main reasons for chemotherapy failure (21). Therefore, it is of great clinical significance to elucidate the mechanism underlying the development of drug resistance of tumor cells, in order to reverse this process and improve the sensitivity of tumor cells to chemotherapeutic agents (22).…”
Section: Mirnas and Chemotherapy For Crcmentioning
confidence: 99%